Emotions, technology, and learning - Tettegah, Sharon Y.; McCreery, Michael P. (Emotions and technology, 2015)
Research suggests two important roles of emotion related to learning and technology.ïÅư First, emotion can be the key factor that is being learned or taught through technological means. Second, emotional responses with and through technology can alter what is being learned or how the content is learned.ïÅư The goal of this volume is to compile and synthesize research that addresses these two perspectives by focusing on the relationship between emotion and learning as facilitated by technology. The book is divided into four sections to represent the specific interest related to emotion and learning: Theory and Overview of Emotions and Learning; Emotions and Learning Online; Technology for Emotional Pedagogy with Students; and Technology of Emotional Pedagogy with Teachers